Association of Polymorphisms in miRNA Processing Genes With Type 2 Diabetes Mellitus and Its Vascular Complications in a Southern Chinese Population - Wen, Zihao; Zou, Xiaoqian; Xie, Xin; Zheng, Shaoling; Chen, Xiaojing; Zhu, Kehui; Dong, Shirui; Liang, Jiayu; Huang, Xiuxia; Liu, Dandan; Wang, Yao; Liu, Yumei; et al. (Frontiers in Endocrinology, 2019)
Abstract Objective: To evaluate the potential association between the genetic variants in miRNA processing genes (RAN, XPO5, DICER1 and TARBP2) and susceptibility to type 2 diabetes mellitus (T2DM) and its vascular complications, as well as to further investigate their interaction with environmental factors in type 2 diabetes. Methods: We conducted a case-control study in genotyping of five polymorphic loci, including RAN rs14035, XPO5 rs11077, DICER1 rs13078, DICER1 rs3742330 and TARBP2 rs784567, in miRNA processing genes to explore the risk factors for T2DM and diabetic vascular complications. Haplotype analyses, interactions of gene-gene and interactions of gene-environment were performed too. Results: We identified a 36% decreased risk of developing T2DM in individuals with the minor A allele in DICER1 rs13078 (OR: 0.64; 95%CI: 0.42-0.95; P: 0.026). The AA haplotype in DICER1 was also associated with a protective effect on T2DM compared with the AT haplotype (OR: 0.63; 95%CI: 0.42-0.94; P value: 0.023). T2DM patients with the TT+TC genotype at RAN rs14035 had a 1.89-fold higher risk of developing macrovascular complications than patients with the CC genotype (OR: 1.89; 95%CI: 1.04-3.45; P value: 0.037). We also identified two three-factor interaction models. One is a three-factor (DICER1 rs13078, body mass index (BMI) and triglyceride (TG)) interaction model for T2DM (OR: 5.93; 95%CI: 1.25-28.26; P = 0.025). Another three-factor (RAN rs14035, hypertension (HP) and duration of T2DM (DOD)) interaction model was found for macrovascular complications of T2DM (OR=41.60, 95%CI=11.75-147.35, P<0.001). Conclusion: Our study provides new evidence that two single nucleotide polymorphisms (SNPs) of the miRNA processing genes, DICER1 and RAN, and their interactions with certain environmental factors might contribute to the risk of T2DM and its vascular complications in the southern Chinese population.